Pengaruh Persepsi Risiko, Manfaat Dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Online Pada Aplikasi Shopee - Salsabila, Hana Zahra; Susanto, Susanto; Hutami, Lusia Tria Hatmanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the effect of perceived risk, benefit and ease of use on purchasing decisions. This study uses four variables, namely risk, benefit and ease of use as independent variables, and purchasing decisions as the dependent variable. The population in this study were active students of the economics faculty at the Sarjanawiyata Tamansiswa Yogyakarta University who used the Shopee application, who were then sampled as many as 120 respondents. The sampling method using purposive sampling with data collection using a questionnaire. The results showed that the risks, benefits and ease of use simultaneously had a significant effect on online purchasing decisions at Shopee, risk had a significant negative effect on online purchasing decisions at Shopee, benefits had a significant negative effect on online purchasing decisions at Shopee, ease of use has a significant effect on online purchasing decisions at Shopee.